2009
DOI: 10.1111/j.1600-0854.2009.00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Hitchhiking of Cu/Zn Superoxide Dismutase to Peroxisomes – Evidence for a Natural Piggyback Import Mechanism in Mammals

Abstract: Most newly synthesized peroxisomal proteins are imported in a receptor-mediated fashion, depending on the interaction of a peroxisomal targeting signal (PTS) with its cognate targeting receptor Pex5 or Pex7 located in the cytoplasm. Apart from this classic mechanism, heterologous protein complexes that have been proposed more than a decade ago are also to be imported into peroxisomes. However, it remains still unclear if this so-called piggyback import is of physiological relevance in mammals. Here, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 48 publications
1
97
0
Order By: Relevance
“…We speculate this dependency arises because the copper-zinc SOD is a constituent enzyme of the peroxisome matrix, which is essential for its dismutase and peroxidase function (Titorenko and Mullen, 2006;Islinger et al, 2009). Deletions in other peroxisomal genes have also recently been shown to sensitize to low-iron conditions, possibly because of an elevated requirement for peroxisomal -oxidation in energy production when iron-dependent mitochondrial energy production is impaired (Jo et al, 2009).…”
Section: Disease Models and Mechanisms Dmmmentioning
confidence: 99%
“…We speculate this dependency arises because the copper-zinc SOD is a constituent enzyme of the peroxisome matrix, which is essential for its dismutase and peroxidase function (Titorenko and Mullen, 2006;Islinger et al, 2009). Deletions in other peroxisomal genes have also recently been shown to sensitize to low-iron conditions, possibly because of an elevated requirement for peroxisomal -oxidation in energy production when iron-dependent mitochondrial energy production is impaired (Jo et al, 2009).…”
Section: Disease Models and Mechanisms Dmmmentioning
confidence: 99%
“…Although SOD1 is generally regarded as a cytosolic protein, some reports have shown that it can be found in the mitochondrial intermembrane space (37,38). A recent report has identified SOD1 in a peroxisomeenriched subcellular fraction and, based on immunofluorescence microscopy studies on cells overexpressing both SOD1 and "copper chaperone of SOD1," concluded that copper chaperone of SOD1 mediates import of SOD1 into peroxisomes (39).…”
Section: Discussionmentioning
confidence: 99%
“…This has originally been attributed to a potential third type of peroxisomal targeting signals (PTS3), but this signal has never been characterized and the import either depends on a PTS-independent interaction with a receptor protein (Klein et al, 2002) or on co-import of proteins (piggy-back), which is a specific property of peroxisomal import (Yang et al, 2001;Subramani, 2002;van der Klei and Veenhuis, 2006;Islinger et al, 2009). …”
Section: Peroxisomal Targeting Signalsmentioning
confidence: 99%